Identifikasi Ketidaklengkapan Pengisian Dokumen Rekam Medis Rawat Jalan Berdasarkan Teori Motivasi Ekspektansi - Revitasari, Alvina (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
Completeness of medical record documents becomes important because it describe the practice of quality services. East Java Community Eye Hospital have problems with completeness of medical record documentation. Incompleteness medical record documentation of outpatient at East Java Community Eye Hospital was rated at 87, 67%.The object of this study was to identification the incompleteness of medical record documentation of outpatient based on Victor Vroom expectancy theory motivation at East Java Community Eye Hospital. The present study conducts a cross-sectional, descriptive research during May 2016 through to use questionnaires and observation on medical record documentation of outpatient. The respondent of this study were personnel who were filling the outpatient medical record documentation. These people were 5 doctors, 5 refractions, and 6 nurses. The result of the study showed that Filling of the medical record documentation at East Java Community Eye Hospital was low. Motivation has driving factor to the incompleteness of outpatient medical record documentation at East Java Community Eye Hospital. Suggestions given to monitoring the performance to complete the medical record documentation of outpatient. Keywords: hospital, incompleteness, medical record, motivation, outpatient, victor vroom.